1988
DOI: 10.1111/j.1399-0039.1988.tb01656.x
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphism of HLA antigens in the Chinese

Abstract: Remarkable differences were observed in antigen frequencies (AF), gene frequencies (GF) and haplotype frequencies (HF) when 2441 healthy Chinese individuals representing nine different ethnic groups and living in 14 different geographic locations were examined for the genetic distribution of the various HLA Class I and II markers. A sizable number of individuals of each ethnic group within each of the three major categories of the Chinese population, namely, Hans, Mongols, and Southern minorities, have been st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…We first identified two unusually strong HLA-A11-restricted epitopes within the Epstein-Barr nuclear antigen EBNA3B as encoded by the type 1 Caucasian prototype strain B95.8; these were the immunodominant IVTDFSVIK epitope (EBNA3B codons 416 to 424, called IVT) and the next most dominant AVFDRKSDAK epitope (EBNA3B codons 399 to 408, called AVF) (7,8). Interestingly, these sequences were often mutated in EBV strains prevalent in the populations of lowland Papua New Guinea (6) and southern China (7), both areas where more than 50% individuals carry the HLA A11 allele (15). Furthermore, when the IVT mutations were examined, the corresponding peptide showed reduced affinity for the HLA A11 peptide binding groove as a result of amino acid changes in the primary anchor positions, 2 and 9, where amino acid side chains interact with binding pockets in the groove (16,29).…”
mentioning
confidence: 99%
“…We first identified two unusually strong HLA-A11-restricted epitopes within the Epstein-Barr nuclear antigen EBNA3B as encoded by the type 1 Caucasian prototype strain B95.8; these were the immunodominant IVTDFSVIK epitope (EBNA3B codons 416 to 424, called IVT) and the next most dominant AVFDRKSDAK epitope (EBNA3B codons 399 to 408, called AVF) (7,8). Interestingly, these sequences were often mutated in EBV strains prevalent in the populations of lowland Papua New Guinea (6) and southern China (7), both areas where more than 50% individuals carry the HLA A11 allele (15). Furthermore, when the IVT mutations were examined, the corresponding peptide showed reduced affinity for the HLA A11 peptide binding groove as a result of amino acid changes in the primary anchor positions, 2 and 9, where amino acid side chains interact with binding pockets in the groove (16,29).…”
mentioning
confidence: 99%
“…4) studies by Lee et al [22] in 1988 showed significant differences in HLA antigen frequencies between the northern and southern Han in China. Consistently, a comprehensive study of immunoglobulin allotypes found the heterogeneity of Han nationality, and confirmed the hypothesis that modern Chinese nation originated from different populations, one originating in the Yellow River valley and the other in the Yangtze River valley [23].…”
Section: Discussionmentioning
confidence: 96%
“…The reported distribution of class II HLA in Chinese is not consistent because of China's huge territory and ethnic heterogeneity [36]. DR4 is one of the most common DR antigens in Han Chinese.…”
Section: Dr4 In Chinesementioning
confidence: 99%
“…However, its phenotype frequency can be as low as 11.0% [37] or as high as 41.7% [36] in different regions. Most reported frequencies have been between 23.9 and 41.0% [36,[38][39][40][41][42][43][44]. In our adult controls the DR4 phenotype frequency was 32.5% (39/120) which is in agreement with the above-mentioned reports.…”
Section: Dr4 In Chinesementioning
confidence: 99%